Preparation and evaluation of SiO(2)-deposited stearic acid-g-chitosan nanoparticles for doxorubicin delivery - Yuan, Hong (Dove Medical Press, 2012)
PURPOSE: Both polymer micelles and mesoporous silica nanoparticles have been widely researched as vectors for small molecular insoluble drugs. To combine the advantages of copolymers and silica, studies on the preparation of copolymer-silica composites and cellular evaluation were carried out. METHODS: First, a stearic acid-g-chitosan (CS-SA) copolymer was synthesized through a coupling reaction, and then silicone oxide (SiO(2))-deposited doxorubicin (DOX)-loaded stearic acid-g-chitosan (CS-SA/SiO(2)/DOX) nanoparticles were prepared through the sol-gel reaction. Physical and chemical properties such as particle size, zeta potential, and morphologies were examined, and small-angle X-ray scattering (SAXS) analysis was employed to identify the mesoporous structures of the generated nanoparticles. Cellular uptake and cytotoxicity studies were also conducted. RESULTS: CS-SA/SiO(2)/DOX nanoparticles with different amounts of SiO(2) deposited were obtained, and SAXS studies showed that mesoporous structures existed in the CS-SA/SiO(2)/DOX nanoparticles. The mesoporous size of middle-ratio and high-ratio deposited CS-SA/SiO(2)/DOX nanoparticles were 4–5 nm and 8–10 nm, respectively. Based on transmission electron microscopy images of CS-SA/SiO(2)/DOX nanoparticles, dark rings around the nanoparticles could be observed in contrast with CS-SA/DOX micelles. Furthermore, CS-SA/SiO(2)/DOX nanoparticles exhibited faster release behavior in vitro than CS-SA/DOX micelles; cellular uptake research in A549 indicated that the CS-SA/SiO(2)/DOX nanoparticles were taken up by A549 cells more rapidly, and that CS-SA/SiO(2)/DOX nanoparticles entered the cell more easily when the amount of SiO(2) was higher. IC(50) values of CS-SA/DOX micelles, CS-SA/SiO(2)/DOX-4, CS-SA/SiO(2)/DOX-8, and CS-SA/SiO(2)/DOX-16 nanoparticles against A549 cells measured using the MTT assay were 1.69, 0.93, 0.32, and 0.12 μg/mL, respectively. CONCLUSION: SiO(2)-deposited stearic acid-g-chitosan organic–inorganic composites show promise as nanocarriers for hydrophobic drugs such as DOX.